Japanese quail (Coturnix japonica) as a model of accelerated aging of human retinal processes. Report 1. Assessment of the age RPE lipofuscin accumulation depending on the retinal amount of oxycarotenoids - P.P. Zak; A.V. Zykova; N.N. Trofimova; M.A. Ostrovsky (Офтальмохирургия, 2013)
ABSTRACT